Woman Empowerment Waste Management with RUTTELA and Vlog Pulo Kodok in Panggung Village Kota Tegal - Yulia Isti Damayanti; Annata Rifqi Leo Rinaldi; Tika Aprilliani; Sesya Dias Mumpuni (Universitas Pancasakti Tegal, 2021)
Benefits for the Community is to obtain the help of thought and energy, as well as science, technology and art in planning and implementing the development of kkn target villages physically and non-physically. Gaining experience in exploring and growing the potential contained in the community so as to actively participate in the progress of village development target kkn. Benefiting and assisting students in implementing programs and development under the responsibility of the entire UPS TEGAL Alternative KKN team. Pancasakti University obtains feedback as the integration of students with the process of village development in the community, so that the curriculum, lecture materials and science development that the University has can better match the real demands of development in the community. Acquire a variety of valuable cases that can be used as an example in providing lecture materials and finding various problems for research development. Improving, expanding and accelerating cooperation with other agencies and departments through the cooperation of students who conduct Real Work Lectures (KKN).